MODEL PENGEMBANGAN VALUE CHAIN MANAGEMENT (VCM) SEBAGAI SOLUSI MENINGKATKAN PRODUKSI PERTANIAN - Deki Fermansyah; Nur Choirul Afif (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2017)
Agriculture product in Indonesia has been happening with problem of low production and scarcity. Due to the low production and scarcity is not limited to just a matter of demand and supply but distribution process, planting schedules product, harvest schedule, seeds are use also took part in the emmergence of this low production. This study aims to (1) map the factor that cause the low production and scarcity of agriculture product and (2) analyze the model of Value Chain Management/VCM in agriculture industry. The research method used in this study is a descriptive analysis method. The data collection process itself is performed by in the depth intrerviews with informants( farmer, collector farmer “poktan/gapoktan”, surveyor farmer “ppl” and institutions. From the in depth interview, the main problem is about ecosystem, harvest schedule, production process and until the product to consumer. Then refer to the reality its, this study result to develop a model of Value Chain Management/VCM product development agriculture can accommodate the interests of all parties as solution to the common problem of low production.